2022
DOI: 10.1099/ijsem.0.005339
|View full text |Cite|
|
Sign up to set email alerts
|

Halalkalibacterium roseum gen. nov., sp. nov., a new member of the family Balneolaceae isolated from soil

Abstract: A Gram-stain-negative, non-motile, moderately halophilic and facultatively anaerobic bacterium, designated YR4-1T, was isolated from a saline-alkali and sorghum-planting soil sample collected in Dongying, Shandong Province, PR China. Growth occurred at 28–45 °C with the presence of 4.0–20.0 % (w/v) NaCl and pH 6.0–9.0. Phylogenetic analysis based on the 16S rRNA gene sequences revealed that YR4-1T shared the highest similarity of 92.1–92.4 % with the valid published species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…For the deeper layers, the biomarkers revealed by LEfSe analysis correspond to OTUs affiliated with halophilic bacteria found in hypersaline ecosystems. They include Coxiella, Anaerophaga, and Balneolaceae for layer L2, exhibiting anaerobic metabolism (Song et al, 2021;Wu et al, 2022). This finding is in agreement with the reversed redox gradient observed in the Salineta wetland.…”
Section: Discussionsupporting
confidence: 85%
“…For the deeper layers, the biomarkers revealed by LEfSe analysis correspond to OTUs affiliated with halophilic bacteria found in hypersaline ecosystems. They include Coxiella, Anaerophaga, and Balneolaceae for layer L2, exhibiting anaerobic metabolism (Song et al, 2021;Wu et al, 2022). This finding is in agreement with the reversed redox gradient observed in the Salineta wetland.…”
Section: Discussionsupporting
confidence: 85%
“…The family Balneolaceae ( Xia et al, 2016 ) belongs to the phylum Balneolota , class Balneolia ( Munoz et al, 2016 ), and includes six genera: Aliifodinibius , Balneola , Fodinibius , Gracilimonas , Halalkalibaculum , and Rhodohalobacter ( Parte et al, 2020 ), which are found in marine and hypersaline environments, such as deep-sea sediments, salt-mines, salterns, and saline soils ( Urios et al, 2006 ; Choi et al, 2009 ; Wang et al, 2012 , 2013 ; Cho et al, 2013 ; Xia et al, 2017 ; Wu et al, 2022a , b ). The genus Fodinibius was proposed in 2012 based on a single species, Fodinibius salinus ( Wang et al, 2012 ) and the genus Aliifodinibius was firstly described only one year later ( Wang et al, 2013 ), including at that time two species, Aliifodinibius roseus (type species) and Aliifodinibius sediminis .…”
Section: Introductionmentioning
confidence: 99%
“…Although traditional cultivation techniques have led to the isolation and description of hundreds of new groups of halophilic bacteria and archaea ( 19 , 22 30 ), a great number of recent culture-independent studies from hypersaline habitats have revealed the prominence of several yet-uncultivated lineages in these systems ( 31 34 ). Most of these uncultivated groups represent dominant populations in hypersaline environments ( 31 , 32 , 35 , 36 ), and are presumably slow growing and fastidious to isolate microorganisms.…”
Section: Introductionmentioning
confidence: 99%